Razumevanje športne vadbe skozi vidik statičnega sistema - Ušaj, Anton (Šport (Ljubljana), 2019)
Two models for prediction performance of 800 m running were constructed and veryfied by using data-base and results from the research experiment on 800 m runners (Šturm, J., Ušaj A., 1985) and by using data from follow-up study during selected competition season. The aim of the study was to simulate 800 m running performance by using different enhancements of performance characteristics: vmax, v400 and v12min. The results have shown that the regression model succesfully predicted performance of 800 m runners. Power of each of the performance characteristics have shown that all are important in prediction of 800 m running. This is particularly important during observation of shorter duration of running at highest running velocities when simulation of world record was the aim of analysis. Namely, the importance of endurance performance even enhanced in parallel to increased maximal velocity and anaerobic endurance. Differently, the velocity model have shown more sensitivity to individual adaptations on training. This model seems to be very useful in simulation of running performance by using enhancements in performance characteristics.
Keywords: 800 m running; hitrostni model; regresijski model; regression model; simulacije; simulations; sport; statical systems; statični modeli; šport; tek na 800 m; velocity model